The Influence of Work Environment and Job Satisfaction on Turnover Intention PT. Intimegah Bestari Pertiwi - Tito Rahmayang; Roswaty Roswaty; Muhammad Bahrul Ulum (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine: The effect of the work environment on the turnover intention of PT. Intimegah Bestari Pertiwi, Effect of Job Satisfaction on Employee Turnover Intention of PT. Intimegah Bestari Pertiwi, Effect of work environment and job satisfaction on employee turnover intention of PT. Intimegah Bestari Pertiwi.This research is a survey research with a quantitative approach. The sample of this research are employees of PT. Intimegah Bestari Pertiwi, totaling 40 employees with purposive sampling technique. Data collection used a questionnaire while data analysis was carried out using multiple linear regression. The results of the investigation show that partially the work environment has no effect on turnover intention. Simultaneously the Work Environment and Job Satisfaction have a positive and significant effect on Turnover Intention.